PENAMPAKAN DUYUNG (DUGONG SIGHTING) DI KEPULAUAN SPERMONDE SULAWESI SELATAN - Priosambodo, Dody; Nurdin, Nadiarti; Amri, Khairul; Massa, Yusran Nurdin; Saleh, Amrullah (Jurnal Ilmu Kelautan SPERMONDE, 2017)
Dugong is the only herbivory mammals in the sea and mainly feed on seagrasses. Population of dugong tends to decrease in all ofits range as an impact from hunting, fishing activities and habitat degradation. In South Sulawesi-Indonesia, recent informationabout dugong population is unknown due to limited observation. Last dugong existence reported from Barranglompo Island in1991. This research aim to reveal the existence of dugong in Spermonde Archipelago. Result of this study showed from 1992to 2017, only 6 individu of dugong were observed. In 2006, one live dugong accidentally found roaming near Samalona Island.This encounter was successfully recorded by video camera. Four years later, one dead dugong found trapped in fishing net nearLantangpeo village, Tanakeke Island and sold to local fishermen for consumed. In 2014, one dugong grazing track was alsofound in Tanakeke Island near Balandatu Village. Information from 2016, reported two dugongs in seagrass meadow aroundPuntondo and Laikang Bay. Last report on 31 January 2017, showedone decomposed body from young dugong stranded inBarranglompo Island. The death cause remaining unknown. From interview with some witnesses and local fishermen, dugongaccidentaly found trapped, drown and dead in fishing net that set up around seagrass meadow. Captured dugong will on sale andslaughtered for its meat.With only once encountered alive in 25 years (which recorded by video camera), it can be concludedthat dugong population in Spermonde archipelago were extremely rare, heavily threatened and facing extinction.Keywords: dugong, sighting, Spermonde Archipelago, South Sulawesi